Parenteral Antipsychotic Choice and Its Association With Emergency Department Length of Stay for Acute Agitation Secondary to Alcohol Intoxication. (3rd July 2018) - Cole, Jon B.; Klein, Lauren R.; Martel, Marc L.
Abstract: Background: Acute agitation secondary to alcohol intoxication frequently requires parenteral sedatives for patient and caregiver safety. Antipsychotics play a prominent role; however, no consensus exists regarding the ideal agent. One important consideration when evaluating the choice of antipsychotic is its association with emergency department (ED) length of stay (LOS). Objectives: We sought to determine the median ED LOS for patients receiving a single parenteral dose of an antipsychotic for acute agitation secondary to alcohol intoxication in an urban Level I trauma center. Methods: This was a retrospective review of patients receiving a single parenteral dose of droperidol, haloperidol, or olanzapine who were acutely intoxicated on alcohol from 2011 to 2016. Patients needing psychiatric assessment in our ED are discharged to a geographically separate department; thus, ED LOS is minimally impacted by waits for psychiatric assessment. Data were abstracted from the electronic medical record and are presented descriptively. Results: A total of 40, 601 patients were identified and screened; 24, 319 patients were intoxicated but received no sedation. Of those remaining 4, 495 received multiple drugs and/or benzodiazepines leaving 11, 787 for analysis. Median age was 42 years, 76% were male, and 5% of patients were admitted. Mean breath ethanol concentration was 227 mg/dL. Antipsychotics administered were as follows: droperidol ( n  = 3, 790), haloperidol ( n  = 1, 449), and olanzapine ( n  = 6, 548). Median ED LOS was shortest for droperidol (499 minutes, 95% confidence interval [CI] = 493–506 minutes), which was significantly shorter than both haloperidol (524 minutes, 95% CI = 515–537 minutes) and olanzapine (533 minutes, 95% CI = 528–539 minutes). No cases of sudden cardiac death occurred. Conclusion: Droperidol, when given as monotherapy for sedation of acute agitation secondary to alcohol intoxication, was associated with significantly shorter ED LOS than either parenteral haloperidol or parenteral olanzapine. No difference in ED LOS was observed between haloperidol and olanzapine.